Дослідження автоматизації поліграфічного виробництва за допомогою цифрових систем управління - Вовк, О. В.; Гаращук, Є. В.; Григор’єв, О. В. (ТОВ «Видавництво Ліра-К», 2025)
The paper explores the integration of digital control systems into printing production processes. It analyzes their impact on efficiency, quality, and adaptability. Case studies and recent advancements in automation technologies are discussed.
Keywords: printing production; поліграфія